1989
DOI: 10.1084/jem.169.6.2227
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory properties of recombinant tumor necrosis factor in rabbit skin in vivo.

Abstract: We have investigated the ability of recombinant TNF (mouse and human) to produce acute inflammatory lesions in an established experimental model of inflammation. Upon intradermal injection in rabbit skin, TNF, in amounts as low as 3 x 10(-14) mol/site, was found to be very potent at inducing local neutrophil accumulation and neutrophil-dependent oedema formation, thereby fulfilling two important criteria to be considered as an inflammatory mediator. Our findings further indicate that the pro-inflammatory prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 14 publications
1
30
0
1
Order By: Relevance
“…Although our light microscopy studies indicated that the leukocytic infiltration was not massive, the ultrastructural studies clearly revealed an increase in leukocytes in transgenic versus control skin. Furthermore, our results are in agreement with a number of recombinant TNFa studies demonstrating that this factor, directly, indirectly, or synergistically, promotes chemotaxis and antimicrobial activity of neutrophils, macrophages, and eosinophils (Rothstein and Schreiber 1988;Sharpe et al 1988;Tracey et al 1988;Munro et al 1989;Rampart et al 1989).…”
Section: Tnfa Overexpression Leads To a Myriad Changes In The Skin Psupporting
confidence: 81%
See 1 more Smart Citation
“…Although our light microscopy studies indicated that the leukocytic infiltration was not massive, the ultrastructural studies clearly revealed an increase in leukocytes in transgenic versus control skin. Furthermore, our results are in agreement with a number of recombinant TNFa studies demonstrating that this factor, directly, indirectly, or synergistically, promotes chemotaxis and antimicrobial activity of neutrophils, macrophages, and eosinophils (Rothstein and Schreiber 1988;Sharpe et al 1988;Tracey et al 1988;Munro et al 1989;Rampart et al 1989).…”
Section: Tnfa Overexpression Leads To a Myriad Changes In The Skin Psupporting
confidence: 81%
“…At lower levels, TNFe~ plays an important protective role in infectious diseases, stimulating chemotaxis and the antimicrobial activity of neutrophils, macrophages, and eosinophils (Sharpe et al 1988;Tracey et al 1988;Munro et al 1989;Rampart et al 1989). That TNFoL is the mediator of these pleiotropic responses has been demonstrated by neutralizing the effects with anti-TNFa antibodies Piguet et al 1987;Tracey et al 1987;Keffer et al 1991).…”
Section: Tnfa Action: Direct Vs Redirect Effectsmentioning
confidence: 99%
“…47 Specifically, TNF␣-induced neutrophil accumulation was fast (maximum within 30 minutes), similar to responses induced by the chemoattractants fMLP or LTB 4 , and the response elicited by IL-1␤ was slow (maximum within 3 to 4 hours) and protein-synthesisdependent. 47,48 In summary, with the use of PECAM-1-deficient mice, the results of the present study clearly demonstrate a role for PECAM-1 as a regulatory molecule in leukocyte migration through vessel walls at sites of inflammation. However, our findings also highlight the fact that PECAM-1-independent leukocyte migration can occur in a temporal-and/or stimulusspecific manner.…”
Section: Discusssionmentioning
confidence: 86%
“…As expected, the magnitude of LTN-induced infiltration of NK cells and T cells was greater than that of neutrophils and macrophages in control NS animals (26). In contrast, the magnitude of TNF-␣-induced infiltration of neutrophils and macrophages was greater than that of NK cells and T cells in control NS animals (27,28). Sponges were retrieved at 6, 24, 48, and 72 h after implantation.…”
Section: Acute Stress Further Enhances Ltn-and Tnf-␣-directed Leukocytementioning
confidence: 99%